ECONOMIC REVIEW OF LIGHTWEIGHT STEEL USE FOR ROOF CONSTRUCTION ON CONSTRUCTION PROJECTS IN THE PALANGKA RAYA UNIVERSITY IN 2017 - Samuel Layang (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
This research aimed to determine the cost of roof construction using lightweight steel and wood on construction projects at the University of Palangka Raya year 2017. This study uses secondary data in the form calculation of the Budget Plan (RAB) and the price of wage units and materials that issued by the Government of Palangka Raya. The analyzing unit price based on the Regulation of Minister of Public Works and Public Housing of Republic of Indonesia No 28 / PRT / M / 2016 concerning Guidance of Unit Price Analysis of Work of Public Works Division. The unit price calculation of the wooden roof construction is using saddle roof model with span 6 m, horses use wood 5/10 with slope 300. Light steel isbusing canal profile with height 75 mm, width 35 mm and thick 0,75 mm. Based on the results of analysis and calculation, the roof construction cost which uses wood is Rp. 231,922.36/m2 and the roof construction cost using light steel of Rp. 184.021,98/m2. The cost of roof construction using light steel is cheaper 26,03% than wooden roof construction